The selective impairment of the perception of first-order motion by unilateral cortical brain damage. - Vaina, L; Makris, N; Kennedy, D; Cowey, A (1998)
First-order (Fourier) motion consists of stable spatiotemporal luminance variations. Second-order (non-Fourier) motion consists instead of spatiotemporal modulation of contrast, flicker, or spatial frequency. In spite of extensive psychophysical and computational analysis of the nature and relationship of these two types of motion, it remains unclear whether they are detected by the same mechanism or whether separate mechanisms are involved. Here we report the selective impairment of first-order motion, on a range of local and global motion tasks, in the contralateral visual hemifield of a patient with unilateral brain damage centered on putative visual areas V2 and V3 in the medial part of the occipital lobe. His perception of second-order motion was unimpaired. As his disorder is the obverse of that reported after damage in the vicinity of human visual area MT (V5), the results support models of motion processing in which first- and second-order motion are, at least in part, computed separately at the extrastriate cortical level.